Middle Pliocene hominin distribution patterns in Eastern Africa. Issue 147 (October 2020) - Villaseñor, Amelia; Bobe, René; Behrensmeyer, Anna K.
Abstract: Abundance distributions of large mammals are underused in exploring how ecological pressures vary across contemporaneous sites in the fossil record. To investigate variation in relative abundance across contemporaneous Pliocene mammal communities, we examine the time interval between ∼3.6 and 3.22 Ma at four sites in the Afar and Turkana basins: Hadar and the lower Omo Valley in Ethiopia and East Turkana and West Turkana in Kenya. Taphonomic and collection biases are examined using skeletal parts, body size, and taxonomic data from database collections. Taphonomic biases due to geologic conditions and fossil collection affected all sites, but those in the Turkana Basin appeared particularly affected by collecting bias. As a result, hominin relative abundance is calculated separately using a taphonomic control taxon, which shares similar collection biases and size. Comparisons of mammalian taxonomic groups revealed that the Omo region was dominated by suids and cercopithecids. The other sites are dominated by open habitat and mixed habitat associated bovids. Hominins had higher abundance wherein the dominant mammal taxa indicate a mix of woodland and grassland environments (Hadar) and were rarer at sites where the majority of taxa are associated with woodland vegetation (the Omo Valley). West Turkana is characterized by mixed habitats and the highest relative abundance of hominins relative to control taxa, but sampling issues due to the collection and reporting of papionins likely drive this result. East Turkana has few hominins relative to the control taxon and has dominant habitats indicative of floodplain grasslands but has a small sample size compared with the other sites. These analyses suggest that Kenyanthropus platyops and Australopithecus afarensis inhabited similar types of habitats across different rift basins. Most convincingly, this study contributes to a growing body of evidence suggesting that early hominins diverged from their great ape counterparts by abandoning woodland-dominated habitats.